Beyond ESAP (Radix Consultants, 1996)
This report emphasizes the need to design an alternative development model to the Economic Structural Adjustment Programme (ESAP) in Zimbabwe. While acknowledging that SAPs are necessary, the study shows that they are insufficient in fostering development (that is, growth with equity). Zimbabwe's economy is characterized by a number of structural rigidities such as unequal access to land and finance whilst a large proportion of its population is engaged in the informal sector. It is the contention of the report that under such conditions, there is nothing inherent in ESAP policies that will lead to development. The main focus of the report, as opposed to SAPs, is to redefine the role of the state in the economy. While SAPs emphasize the rolling back of the state, this report is rooted in the premise that market failures are rampant in most less developed countries, including Zimbabwe. The state needs to intervene in factor markets, in the development of industrial and technological capabilities in order to foster competitiveness, etc, so as to deal with such market failures. (DÜI-Hff)
Keywords: Graue Literatur; Entwicklungsstrategie; Landwirtschaftliche Entwicklung; Industrialisierung; Arbeitsmarkt; Finanzsektor; Wirtschaftliche Anpassung; Simbabwe; Wirtschaftspolitik; Wirtschaftsreform; Strukturanpassung; Wirkung; Auswirkung; Entwicklungsmodell; Alternative